2007
DOI: 10.1093/aob/mcl272
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cultured Primary Roots Derived from Stem Segments of Cassava ( Manihot esculenta ) Can Behave Like Storage Organs

Abstract: The storage root formation system reported here is a first approach to develop a tuberization model, and additional efforts are required to improve it. Although it was not possible to achieve root secondary growth, after this work it will be feasible to advance in some aspects of in vitro cassava tuberization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
3
25
0
4
Order By: Relevance
“…Chromosome counts on adventitious root tips allowed determine the innermost layer constitution, because this roots originate in pericycle, which is derived from L3 layer (Evert, 2007;Medina et al, 2007;Bomfim et al, 2011). On this counting, 54 chromosomes were noted, which confirms the same ploidy of parental species M. fortalezensis.…”
Section: L2 and L3 Layer Constitution By Cytogenetic Analysismentioning
confidence: 52%
“…Chromosome counts on adventitious root tips allowed determine the innermost layer constitution, because this roots originate in pericycle, which is derived from L3 layer (Evert, 2007;Medina et al, 2007;Bomfim et al, 2011). On this counting, 54 chromosomes were noted, which confirms the same ploidy of parental species M. fortalezensis.…”
Section: L2 and L3 Layer Constitution By Cytogenetic Analysismentioning
confidence: 52%
“…3), while it took KMM explants a further two weeks to obtain high quality SE. Combining auxins and cytokinins, during somatic embryo maturation, is essential during cassava regeneration, as these mediate whole plant recovery (Hankoua et al, 2005;Medina et al, 2007). For instance, Fan et al (2011) demonstrated that NAA regulated organ growth; while BA facilitated cell division and elongation in cassava tuberisation.…”
Section: Discussionmentioning
confidence: 99%
“…Success in transformation and regeneration of cassava has been previously reported, with protocols employing different phytohormones and explants, including apical meristems, zygotic embryos, immature leaf lobes and stems (Medina et al, 2007;Fletcher et al, 2011;Rossin and Rey, 2011). While the majority of studies are biased towards use of immature leaf lobes as explants, their occurrence (immature leaf lobes) per parent stock is limited; hence, necessitating the possibility of exploring other plant parts such as stems.…”
Section: Introductionmentioning
confidence: 99%
“…한편 기내에서 자란 식물체에서도 뿌리비대가 관 찰되고 있다. 기내 식물체의 뿌리 비대에 관한 연구로 감자 (Xu et al 1998), yam (Alizadeh et al 1998, 및 cassava (Medina et al 2007) 등에서 보고되어 있다. 기내 식물체의 뿌리 비대는 번식된 개체의 저장 및 운반이 양호하기 때 문에 또 다른 우수한 번식방법이 될 수 있다.…”
unclassified
“…이러한 연 유로 감자에서는 뿌리 비대에 관한 다수의 연구 논문이 있으며 (Koda and Okazawa 1983;Khuri and Moorby 1995;1996;Donnelly et al, 2003), 이 기술을 이용한 대량번식으 로 실용화 되어 있다 (Kim et al 2009b). 기내 비대근 형성은 주로 단자엽 식물인 yam (Alizadeh et al 1998), Curcuma aromatica (Nayak 2000), Curcuma longa (Shirgurkar et al 2001)에서 보고되었고, 쌍자엽 식물에서 는 cassava (Medina et al 2007 형성율을 보였다 (Fig. 1A).…”
unclassified